The confirmed realities and myths about the benefits and costs of 3D visualization and virtual reality in discrete event modeling and simulation: A descriptive meta-analysis of evidence from research and practice. (October 2017) - Akpan, Ikpe Justice; Shanker, Murali
Highlights: Confirmed realities versus myths of 3D/VR in discrete-event simulation and modeling. The 3D/VR improves model quality and contradicts the claims that it adds no value. The 3D/VR is highly potent for model validation, verification, and experimentation. The 3D/VR is significantly valuable for analysis and presentation of results. Creating the 3D/VR model is complex, takes longer, but enhances the project quality. Abstract: The past seventeen years has witnessed a significant transformation in discrete event modeling and simulation, and the introduction of new modeling methodology based on three-dimensional (3D) visualization and virtual reality (VR) technologies. While several studies demonstrate the benefits and costs of 3D and VR modeling in discrete event simulation (DES) based on empirical evidence, others rely on anecdotal evidence and experience from practice. Further, there are still some unsubstantiated claims about the gains and challenges arising from the application of 3D and VR technologies in DES. This paper synthesizes the realized benefits and costs associated with modeling and simulation in 3D and VR while differentiating the realities from claims (myths). The results show that 3D and VR techniques offer significant benefits in the major modeling and simulation tasks than speculated among practitioners in the simulation community.